Menuju Pendidikan Kristiani yang Bersahabat Di Tengah Heterogenitas Agama - Yohanes Krismantyo Susanta (Jurnal Teologi Cultivation, 2020)
The practice of religious education (including Christian religious education) carried out by religious institutions is considered to have contributed to national disunity. This is indicated by the attitude of feeling the most correct self, seeing other people who are different (in the context of religion) as a party that is more inferior so as to bring up the hierarchy (domination-subordination relations) that causes alienation (exclusion) of others. This paper aims to find a friendly form of Christian education in the context of religious heterogeneity. By utilizing the concept of friendship promoted by Jürgen Moltmann, this paper shows that friendship is not just relationships formed in the private sphere but is always conceived and practiced in the public sphere. In Christian Education that promotes friendship, Christians need to transcend borders, transcend church walls and work together with other religious communities for peace and justice.